Femtosecond laser ablation of metal targets: The physical origin of the power law size distribution of nanoparticles. (February 2021) - Wang, Tingyuan; Song, Yuyan; Liu, Chuqian; Wang, Xiaolei; Lin, Lie; Liu, Weiwei; Zhang, Nan
Graphical abstract: Highlights: An analytic model is proposed to predict the final nanoparticle size distribution. The model explains the power law size distribution with a clear physical picture. The nanodroplets' evaporation is the origin of the power law size distribution. The final size distribution and generation process of nanoparticles are bridged. Abstract: Near-infrared femtosecond laser is employed to ablate the copper target in vacuum (10 −4 Pa). The ejected nanoparticles are collected by a silicon substrate. The 3D profiles of the deposited nanoparticles indicate before resolidification on the substrate they are nanodroplets generated by some phase separation process, such as phase explosion or cavitation. To study the nanoparticles' generation dynamics and size distribution, the commonly used methods are the molecular dynamics simulation and the Monte Carlo method. However, the former cannot predict the particle size distribution at the final state and the latter cannot provide a clear physical picture. In this paper, taking both the nanoparticles' generation and ejection into account, an analytical thermodynamic model based on the nanodroplets' evaporation is proposed. In this model, the nanoparticles' sizes are redistributed due to the nanodroplets' evaporation during the flight from the target to the substrate, which provides a clear physical picture and successfully explains the physical origin of the final power law particle size distribution on the substrate. The model bridges the gap between the final size distribution and the thermodynamic generation process of nanoparticles, which will benefit the size control of the ablation-generated nanoparticles.